Characteristics of the phyllosphere microbial community and its relationship with major aroma precursors during the tobacco maturation process - Shi, Yixuan; He, Yuansheng; Zheng, Yuanxian; Liu, Xixi; Wang, Shuzhong; Xiong, Tian’e; Wen, Tao; Duan, Hong; Liao, Xiaolin; Cui, Quanren; Nian, Fuzhao (Frontiers in Plant Science, 2024)
Numerous bacteria, fungi and other microorganisms in the tobacco phyllosphere interstellar area participate in the physiological metabolism of plants by interacting with the host. However, there is currently little research on the characteristics of tobacco phyllosphere microbial communities, and the correlation between tobacco phyllosphere microbial communities and phyllosphere factor indicators is still unknown. Therefore, high-throughput sequencing technology based on the 16S rRNA/ITS1 gene was used to explore the diversity and composition characteristics of tobacco phyllosphere bacterial and fungal communities from different maturation processes, and to identify marker genera that distinguish phyllosphere microbial communities. In this study, the correlations between tobacco phyllosphere bacterial and fungal communities and the precursors of major aroma compounds were explored. The results showed that as the tobacco plants matured, the density of glandular trichomes on the tobacco leaves gradually decreased. The surface physicochemical properties of tobacco leaves also undergo significant changes. In addition, the overall bacterial alpha diversity in the tobacco phyllosphere area increased with maturation, while the overall fungal alpha diversity decreased. The beta diversity of bacteria and fungi in the tobacco phyllosphere area also showed significant differences. Specifically, with later top pruning time, the relative abundances of Acidisoma, Ralstonia, Bradyrhizobium, Alternaria and Talaromyces gradually increased, while the relative abundances of Pseudomonas, Filobassidium, and Tausonia gradually decreased. In the bacterial community, Acidisoma, Ralstonia, Bradyrhizobium, and Alternaria were significantly positively correlated with tobacco aroma precursors, with significant negative correlations with tobacco phyllosphere trichome morphology, while Pseudomonas showed the opposite pattern; In the fungal community, Filobasidium and Tausonia were significantly negatively correlated with tobacco aroma precursors, and significantly positively correlated with tobacco phyllosphere trichome morphology, while Alternaria showed the opposite pattern. In conclusion, the microbiota (bacteria and fungi) and aroma precursors of the tobacco phyllosphere change significantly as tobacco matures. The presence of Acidisoma, Ralstonia, Bradyrhizobium and Alternaria in the phyllosphere microbiota of tobacco may be related to the aroma precursors of tobacco.